Carcass composition and muscle distribution of kambing katjang does - Vidyadaran , M. K.; Razak, A.; Ganesamurty, P. (Malaysian Society of Applied Biology, 1984)
Twelve adult kambing katjang does from two smallholder farms under fairly similar management, ranking from 18.18 to 23.30 kg. liveweight. 2-2½ yrs. old were used in the studies. The dressing percentages ranged from 35.0-44.3% with a mean value of 39.66%. The carcass had high proportions of muscle (71.51%) and bone (20.92%) but a low level of fat (4.19%). The muscle bone ratio was 4.07:1. Standard muscle groups (SMG) values were as follows: 1(31.5%).2(4.3%).3(12.1%). 4(11.5%). 5(12.4%). 6(2.3%). 7 (10.3%). 8 (5.2%) and 9 (9.0%). The percentage of expensive muscle (SMG 1. 3 and I» was 1)1)%. The locomotion and agility indices were 111 and 126 respectively. The percentages of 96 individual muscles is also reported